Propofol Inhibits Lipopolysaccharide-Induced Inflammatory Responses in Spinal Astrocytes via the Toll-Like Receptor 4/MyD88-Dependent Nuclear Factor-κB, Extracellular Signal-Regulated Protein Kinases1/2, and p38 Mitogen-Activated Protein Kinase Pathways. (June 2015) - Zhou, Cheng-Hua; Zhu, Yang-Zi; Zhao, Pan-Pan; Xu, Chun-Mei; Zhang, Ming-Xing; Huang, He; Li, Jing; Liu, Lu; Wu, Yu-Qing
Abstract : BACKGROUND: In this study, we investigated the effect of propofol, a commonly used IV anesthetic, on lipopolysaccharide (LPS)-induced inflammatory responses in astrocytes and explored the molecular mechanisms by which it occurs. METHODS: Astrocytes were stimulated with LPS (1.0 μg/mL) in the absence and presence of different concentrations of propofol. The expression of astrocyte marker glial fibrillary acidic protein (GFAP) in astrocytes was detected using immunofluorescence staining and Western blot analysis. The levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor-α were measured using an enzyme-linked immunosorbent assay. The mRNA level of Toll-like receptor 4 (TLR4) was determined by semiquantitative reverse transcriptase-polymerase chain reaction. The protein expressions of TLR4, myeloid differentiation factor 88 (MyD88), p- extracellular signal-regulated protein kinases (ERK)1/2, p-c-Jun N-terminal kinase, p-p38 mitogen-activated protein kinase (MAPK), p-I-κBα, I-κBα, and p-nuclear factor-κB (NF-κB)p65 were detected by Western blot. RESULTS: Our results show that after stimulation with LPS, the levels of IL-1β, IL-6, and tumor necrosis factor-α and the expression of GFAP in astrocytes were up-regulated significantly. In addition, the expression of TLR4, MyD88, p-ERK1/2, p-c-Jun N-terminal kinase, p-p38 MAPK, and p-NF-κBp65 increased, whereas the expression of total I-κBα decreased upon stimulation with LPS. Propofol (10 μM) reduced the secretion of proinflammatory cytokines, inhibited the expressions of GFAP, TLR4, MyD88, p-ERK1/2, p-p38 MAPK, and p-NF-κBp65 in astrocytes challenged with LPS. CONCLUSIONS: In the present study, propofol 10 μM but not lower clinically relevant or higher supra-clinical concentrations attenuated LPS-induced astrocyte activation and subsequent inflammatory responses by inhibiting the TLR4/MyD88-dependent NF-κB, ERK1/2, and p38 MAPK pathways. Abstract : Published ahead of print February 18, 2015